CRIMINAL LIABILITY IN THE ACT OF THEFT (VIDE ARTICLE 362 KUHP) OF GOLD WHICH IS COMMITTED ON A CONTINUOUS BASIS (VOORTGEZETTE HANDELING VIDE ARTICLE 64 KUHP) - Adistyawan, Fany; Rubaie, Ach; Khoidin, M; Djaja, Dudik (Jurnal Poros Hukum Padjadjaran, 2024)
Continuing actions are a combination of several actions committed by a person, where between one action and another action there has never been a judge's decision that has permanent legal force, so that the perpetrator is subject to a certain method of punishment, as stipulated in article 64 of the Criminal Code. This combined form in Dutch is known as "Voortgezette Handling". The form of continuous action can be identified if a person commits several actions and some of these actions are separate crimes but among these actions, there is such a close relationship with one another that several of these actions must be considered as one continuous action. Continued theft is explained in Article 362 of the Criminal Code Jo Article 64 Paragraph (1) of the Criminal Code. The formulation of the problem in this study is how is the legal responsibility for the crime of gold theft by continuing Article 362 of the Criminal Code in conjunction with Article 64 paragraph (1) of the Criminal Code and law enforcement for the crime of gold theft by continuing Article 362 of the Criminal Code in conjunction with Article 64 Paragraph (1) of the Criminal Code. The type of method applied in this research is normative legal research, where normative legal research is a scientific research procedure to find truth based on scientific logic from a normative perspective. using a statutory regulation approach is analyzed using qualitative normative methods with inductive logic, namely thinking from specific matters to general matters. Criminal responsibility is the responsibility of a person for the crime he has committed. Strictly speaking, that person is responsible for the crime he committed. Thus, the occurrence of criminal liability because there has been a criminal act committed by someone. Criminal responsibility is essentially a mechanism built by criminal law to react to violations of the "agreement to refuse" a certain act.Law enforcement by the Pasuruan Police through investigation and investigation the conclusion that it is strongly suspected that the suspect has violated Article 362 of the Criminal Code in conjunction with Article 64 Paragraph (1) of the Criminal Code. Meanwhile, the basis for the judge's consideration in deciding the case is that the legal facts that emerged during the trial, prove that all the elements of Article 362 Jo. Article 64 paragraph (1) of the Criminal Code has been fulfilled, so the Defendant must be legally and convincingly proven to have committed the crime as charged in the Public Prosecutor's single Indictment.